Distribution of the Eucharist (Holy Communion) - Mumbai Archive Project Team (Jio Institute, 2024)
The table used for distributing the Eucharist (Holy Communion) to the faithful is consecrated and functions as a temporary altar. Such an altar typically includes essential items such as an altar cloth, a crucifix or cross, candles, and the necessary liturgical vessels (chalice, paten, ciborium).